Black Phosphorus: Tuning the Optical and Electrical Properties of Few‐Layer Black Phosphorus via Physisorption of Small Solvent Molecules (Small 47/2019). Issue 47 (20th November 2019) - Wang, Ye; Slassi, Amine; Cornil, Jérôme; Beljonne, David; Samorì, Paolo
Abstract : In article number 1903432, David Beljonne, Paolo Samorì, and co‐workers demonstrate how common solvent molecules could tune the electronic and optical properties of few‐layer black phosphorus. The physisorption of solvent molecules is shown to modulate the charge carrier density, field effect mobility, and Raman peak shift of black phosphorus, originating from charge transfer and molecular dipole doping. The results not only reveal fundamental molecular‐2D materials interaction mechanisms, but also enlighten the choice of solvents for 2D black phosphorus processing for production, functionalization and applications.